PEMANFAATAN BAKTERI RHIZOBIUM TAHAN SALIN DAN KALSIUM UNTUK PENGEMBANGAN TANAMAN LEGUMINOSA PAKAN DI LAHAN PANTAI UTARA JAWA TENGAH - , Eny Fuskhah, Ir.,M.Si., Prof. Dr. Ir. R. Djoko Soetrisno, M. Sc ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The research aim in general was to investigate the unexplored coastal area to legume forage crops for developing livestock field. The result was hoped be able to recommend a new technology for developing livestock in coastal area. In the first study, assessment of soil salinity were conducted in five different locations of Northern Central Java Coast, namely Semarang, Pekalongan, Jepara, Demak, and Rembang. The research showed various level ranged from very low to very high of soil salinity in dry season, July 2006. Demak (Wedung) had the lowest soil salinity that equal to the electrical conductivity (EC) of 0.85 mmhos/cm, the next EC grade was Jepara (Kedung) of 2.2 mmhos/cm, Semarang (Tugu) of 6.4 mmhos/cm, Pekalongan (Pantai Pasir Kencana) of 11.4 mmhos/cm, and the highest Rembang (Kaliori) of 17.5 mmhos/cm. In this step was also able to isolate Rhizobium from turi (Sesbania grandiflora), lamtoro (Leucaena leucocephala), calopo (Calopogonium mucunoides) which were tolerant under high salinity of 8,500 ppm NaCl or equale to electrical conductivity of 15 mmhos/cm. In the second study, test of association selected rhizobium with forage legumes under saline stress condition were done in a glass house. The saline soil tested were taken from coastal area of Tugu Semarang with EC of 6.4 mmhos/cm. Various combination of tolerant saline Rhizobium bacteria isolate were inoculated to 3 groups legume based on its selectivity to Rhizobium need, namely high selectivity (lamtoro/Leucaena leucocephala), low selectivity (Calopogonium mucunoides), and moderate selectivity (Centrosema pubescens). The experiment arranged completely randomized design following factorial 4 x 3 in three times replication. The first factor was kind isolates: I1=without Rhizobium, I2=Rhizobium from calopo, I3=Rhizobium from lamtoro, I4=mix of Rhizobium from calopo and lamtoro. The second factor was kind of legumes: T1=lamtoro, T2=calopo, T3=centro. The results of the study showed, all isolate Rhizobium were able to form effective root nodules of legume and tended to increase growth and production of legumes. The growth and production of legumes were influenced by kind of plant factor. Lamtoro was exhibited growing well when inoculated with Rhizobium inoculum from lamtoro, either Calopogonium when inoculated with Rhizobium inoculum from Calopogonium, while Centrosema responded with Rhizobium inoculum combination from lamtoro and Calopogonium for their growth. The third study following split-split plot 2 x 2 x 2 designed with 3 replication was to investigate the influence of gypsum and Rhizobium to lamtoro and Calopogonium plant in saline soil. The research was held at Morosari Beach Sayung Demak that had electrical conductivity of 20.45 mmhos/cm. The current Rhizobium was tolerant from salinity up to 12,000 ppm NaCl. The main plot was kind of legumes, namely T1 = lamtoro, and T2 = calopo. Sub plot was inoculation rhizobium, namely I1 = without inoculation, and I2 = inoculation tolerance saline rhizobium. While the sub-sub plot, gypsum treatment namely G1 = without gypsum, and G2 = with gypsum. The result showed that Calopogonium was not able to survive to 13rd week in saline soil with EC of 20.45 mmhos/cm with percent of mortality 73,96%. Lamtoro was still survived even short with percent of death 21.35%. It can be concluded that tree legume lamtoro which planted in high level saline soil was more tolerant than cover crop legume Calopogonium. Gypsum and Rhizobium inoculation tended to increase growth and production of legumes in saline land.